Tetragonal Almandine-Pyrope Phase, TAPP: finally a name for it, the new mineral jeffbenite. (2nd January 2018) - Nestola, Fabrizio; Burnham, Antony D.; Peruzzo, Luca; Tauro, Leonardo; Alvaro, Matteo; Walter, Michael J.; Gunter, Mickey; Anzolini, Chiara; Kohn, Simon C.
Abstract: Jeffbenite, ideally Mg3 Al2 Si3 O8, previously known as tetragonal-almandine-pyrope-phase ('TAPP'), has been characterized as a new mineral from an inclusion in an alluvial diamond from São Luiz river, Juina district of Mato Grosso, Brazil. Its density is 3.576 g/cm 3 and its microhardness is ∼7. Jeffbenite is uniaxial (-) with refractive indexes ω = 1.733(5) and ε = 1.721 (5). The crystals are in general transparent emerald green. Its approximate chemical formula is (Mg2 62 Fe 2+ 0.27 )(Al186 Cr0 16 )(Si2 g2 Al018 )O12 with very minor amounts of Mn, Na and Ca. Laser ablation ICP-MS showed that jeffbenite has a very low concentration of trace elements. Jeffbenite is tetragonal with space group I 42 d, cell edges being a = 6.5231(1) and c = 18.1756(3) Å. The main diffraction lines of the powder diagram are [d (in Å), intensity, hkl ]: 2.647, 100, 2 0 4; 1.625, 44, 3 2 5; 2.881, 24, 2 1 1; 2.220, 19, 2 0 6; 1.390, 13, 4 2 4; 3.069, 11, 2 0 2; 2.056, 11, 2 2 4; 1.372, 11, 2 0 12. The structural formula of jeffbenite can be written as (M1)(M2)2 (M3)2 (T1)(T2)2 O12 with M1 dominated by Mg, M2 dominated by Al, M3 dominated again by Mg and both T1 and T2 almost fully occupied by Si. The two tetrahedra do not share any oxygen with each other (i.e. jeffbenite is classified as an orthosilicate). Jeffbenite was approved as a new mineral by the IMA Commission on New Minerals and Mineral Names with the code IMA 2014-097. Its name is after Jeffrey W. Harris and Ben Harte, two world-leading scientists in diamond research. The petrological importance of jeffbenite is related to its very deep origin, which may allow its use as a pressure marker for detecting super-deep diamonds. Previous experimental work carried out on a Ti-rich jeffbenite establishes that it can be formed at 13 GPa and 1700 K as maximum P-T conditions.